2015
DOI: 10.1371/journal.pone.0142740
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Role of Injury-Induced Electric Fields (EFs) in Regulating the Astrocytic Response to Injury in the Mammalian Central Nervous System

Abstract: Injury to the vertebrate central nervous system (CNS) induces astrocytes to change their morphology, to increase their rate of proliferation, and to display directional migration to the injury site, all to facilitate repair. These astrocytic responses to injury occur in a clear temporal sequence and, by their intensity and duration, can have both beneficial and detrimental effects on the repair of damaged CNS tissue. Studies on highly regenerative tissues in non-mammalian vertebrates have demonstrated that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 163 publications
(243 reference statements)
0
19
0
Order By: Relevance
“…The lineage and differentiation state of cells can also modify their response to EFs (Patel and Poo, 1982;Babona-Pilipos et al, 2011;Baer et al, 2015;Li et al, 2015). With respect to NPCs, we have shown that undifferentiated NPCs migrate in the presence of EFs but not their differentiated progeny (Babona-Pilipos et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The lineage and differentiation state of cells can also modify their response to EFs (Patel and Poo, 1982;Babona-Pilipos et al, 2011;Baer et al, 2015;Li et al, 2015). With respect to NPCs, we have shown that undifferentiated NPCs migrate in the presence of EFs but not their differentiated progeny (Babona-Pilipos et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Rat cortical astrocytes migrate anodally and show increased proliferation in an EF of 40 mV/mm (Baer et al, 2015). Nerves and Schwann cells have a galvanotaxis threshold of ca.…”
Section: Interaction Of Ef With Tissue Electroporation Galvanotaxismentioning
confidence: 99%
“…Unlike other studies of electrical stimulation on cultured astrocytes that mostly focused on the applied current amplitude (4 -1500 mV/mm) rather than the frequency (74)(75)(76)(77)(78), this report, to the best of our knowledge, demonstrates for the first time that the mobility of intracellular vesicles in astrocytes can be increased only at a low-frequency electrical stimulation. This frequency-dependent effect of electrical fields on cellular functionalities likely applies to other cell types, such as neurons, microglial, or even cancer cells.…”
Section: Discussionmentioning
confidence: 51%